2018
DOI: 10.1093/jamia/ocy107
|View full text |Cite
|
Sign up to set email alerts
|

A web application to involve patients in the medication reconciliation process: a user-centered usability and usefulness study

Abstract: Our findings highlight the importance and value of user-centered usability testing of a patient application implemented in "real-world" conditions. To achieve adoption and sustained use by patients, the app should meet patients' needs while also efficiently improving the quality of MedRec.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(38 citation statements)
references
References 50 publications
1
29
0
Order By: Relevance
“…Patients were generally satisfied with the patient portal medication reconciliation method, compared to earlier results. 11,12 Although patients in the usual care group were significantly more satisfied with the medication reconciliation method than patients in the patient portal group, the difference was small. Both patient groups indicated that they preferred medication reconciliation at home above medication reconciliation in the hospital.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Patients were generally satisfied with the patient portal medication reconciliation method, compared to earlier results. 11,12 Although patients in the usual care group were significantly more satisfied with the medication reconciliation method than patients in the patient portal group, the difference was small. Both patient groups indicated that they preferred medication reconciliation at home above medication reconciliation in the hospital.…”
Section: Discussionmentioning
confidence: 97%
“…10e13 Patients are generally satisfied with using the patient portal and think that it could improve communication about medication with health care professionals. 12 Although these studies show that patients can have a role in medication reconciliation, to our knowledge no studies have been performed in which the quality of patient portal medication reconciliation was compared to medication reconciliation by a pharmacy professional.…”
mentioning
confidence: 99%
“…Patients who use an online personal health record (PHR)—a secure online website that gives patients access to personal health information—are able to relatively accurately record a list of their medication [ 33 , 34 ]. Although PHRs facilitate patient empowerment and broad implementation of MR, more medication discrepancies are identified with MR performed by a healthcare professional than with an online PHR used by patients [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge of these risk factors will give insight into how to target patients for whom MR can safely be performed through use of a PHR. Currently, only one small study (n = 13) investigated the association between patient characteristics and deviations between the medication list documented by the patient in the PHR, compared to the best possible medication history [ 34 ]. This study did not find an association between risk factors (such as age, sex, previous IT use, number of medications or pattern of use) and the number of deviations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation